Pengaruh Implementasi Sistem Robotik Berbasis Kecerdasan Buatan terhadap Kualitas Produk Pemesinan CNC - Palungan, Musa Bondaris; Kendek, Yohanis Sampe (Fakultas Teknik UMSU, 2025)
This study aims to evaluate the impact of implementing an artificial intelligence (AI)-based robotic system on the quality of CNC machining products at PT Evergrown Technology Batam. A quantitative method was employed using purposive sampling on 25 observation units. The quality parameters analyzed include surface roughness and product cylindricity. Data analysis techniques involved linear regression and ANOVA tests to determine the significance of relationships between variables. The findings indicate that the application of AI technology in robotic systems significantly reduces surface roughness (Y = 2.736 − 0.136X; p 0.001) and improves the cylindricity accuracy of the machined products (Y = 0.075 − 0.005X; p = 0.005). These results suggest that intelligent robotic systems make a substantial contribution to enhancing machining precision and overall product quality. Therefore, the implementation of such technology can serve as a strategic solution to improve quality outcomes in CNC-based manufacturing processes.